Vol.1 - "Parthasarthy, R. (ed.)" (New Delhi, 2006)
An attempt to discern the patterns of developmental paradigms at a regional scale of Western and Central India was planned under FF50-GIDR partnership through a national seminar that was later held in 2003. Scholars and other stakeholders on the developmental scene of Western and Central India contributed on the various yet inter-related aspects to trace the manifold links between policies and programmes. The papers presented, however, eventually forge many additional linkages as well. The seminar metamorphosed into this compendium of select papers reflecting an array of perspectives and empirical analysis. These papers are organised under six themes???Economic Growth and Sustainable Development, Urbanisation and Industrialisation, Social Sector, Management of Common Property Resources, Watershed Development, and Irrigation Management. The scholarly papers in each of these sections???many of them richly empirical??? besides presenting the trends also offer a critique with an aim to inform the policy as well as practice.
Keywords: India - Economic conditions